Comparative study of antimicrobial potential of white tea and black tea leaf extracts from East Java-Indonesia on two species of oral streptococci - Kusumawardani, Anisa; Sukmasari, Susi; Mutalib, Nurul Akmal Abdul; Rahman, Siti Fatihah Abdul; Ichwan, Solachuddin Jauhari Arief (Elsevier, 2019)
Tea leaves have been known to have antimicrobial properties against many types of bacteria. This study was aimed to compare antibacterial activity of white tea and black tea leaf extracts against two cariogenic oral Streptococcus mutans and Streptococcus sobrinus bacteria. Ethanol-based and water-based extracts of white tea and black tea fermented leaves from Wonosari highland tea plantation (East Java, Indonesia) were used in this study. Disk Diffusion Assay was performed to assess the antimicrobial activity of the extracts. The zones of inhibition were measured after 72 hours of incubation period. We found that the ethanolbased and water-based white tea extracts showed significant antibacterial activity against Streptococcus mutans and Streptococcus sobrinus, while ethanol-based and water-based extracts of black tea showed antibacterial effect against Streptococcus mutans only. However, the inhibition zone of ethanol-based and water-based extracts of black tea against Streptococcus mutans were greater compared to white tea. These results indicate the potential health benefit of white tea and black tea for reduction of cariogenic pathogens.